Adoption of the ADA/EASD guidelines in 10 Eastern and Southern European countries: Physician survey and good clinical practice recommendations from an international expert panel. (February 2021) - ,; Banach, Maciej; Gaita, Dan; Haluzik, Martin; Janez, Andrej; Kamenov, Zdravko; Kempler, Peter; Lalic, Nebojsa; Linhart, Ales; Mikhailidis, Dimitri P; Nocoń, Aleksandra; Silva Nunes, Jose; et al.
Abstract: Aims: Evidence from cardiovascular outcomes trials (CVOTs) of glucagon-like peptide-1 receptor agonists and sodium-glucose cotransporter-2 inhibitors was reflected in the most recent guidelines from the American Diabetes Association (ADA) and the European Association for the Study of Diabetes (EASD). The aim of the present study was to assess the adoption of the ADA/EASD guidelines in a convenience sample of physicians from Eastern and Southern Europe, the barriers to the implementation of these guidelines and the measures needed to facilitate their implementation. Methods: Attendees at two international diabetes conferences could volunteer to respond to a fully anonymous survey. Responses were analysed descriptively and a panel of experts from around the region was consulted to interpret the survey results. Results: Responses (n = 96) from 10 countries were analysed. Most participants (63.4%) considered the ADA/EASD guidelines fundamental to their practice. All respondents saw the value of the CVOT-based ADA/EASD recommendations and 77–80% generally implemented them. Measures suggested to improve adherence to the ADA/EASD guidelines included aligning reimbursement policy with the guidelines (54.4%), publishing guidelines in a simple and concise form (42.4%) and translating guidelines into local languages (33.3%). Conclusions: Aligning reimbursement with recent evidence and providing short summaries of the ADA/EASD guidelines in local languages could facilitate physician adherence.